2020
DOI: 10.1177/1359105320906242
|View full text |Cite
|
Sign up to set email alerts
|

Not the exercise type? Personality traits and anxiety sensitivity as predictors of objectively measured physical activity and sedentary time

Abstract: Personality traits have been investigated as predictors of sedentary behavior, while both personality traits and anxiety sensitivity have been investigated as predictors of physical activity; however, few studies employed objective measurement of these behaviors. The current study recruited 64 young adults who completed the Anxiety Sensitivity Index–3 and NEO-Personality Inventory-3, then wore accelerometers for 1 week. Results revealed that agreeableness and anxiety sensitivity were inversely associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The use of two samples and of both accelerometers and self-reports to assess physical activity are the major strengths of this study. Although the PASSWORD sample was relatively inactive and the ERMA sample did not include men, both samples are large compared to previous studies using accelerometers [18][19][20]22] and the results thus contribute to knowledge on the relationship between personality and different measures of physical activity. The ERMA sample showed relatively high amount of MVPA per day (whole day 49.7 ± 25.9 min) compared, for example, to Canadian women aged 40-59 (approximately 24 min/day) [3] and Norwegian women aged 20-64 (36 min/day) [4].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The use of two samples and of both accelerometers and self-reports to assess physical activity are the major strengths of this study. Although the PASSWORD sample was relatively inactive and the ERMA sample did not include men, both samples are large compared to previous studies using accelerometers [18][19][20]22] and the results thus contribute to knowledge on the relationship between personality and different measures of physical activity. The ERMA sample showed relatively high amount of MVPA per day (whole day 49.7 ± 25.9 min) compared, for example, to Canadian women aged 40-59 (approximately 24 min/day) [3] and Norwegian women aged 20-64 (36 min/day) [4].…”
Section: Discussionmentioning
confidence: 91%
“…This is important, especially among older adults whose daily activity is mainly light intensity [17]. Accelerometer studies have not reported consistent associations with personality traits [18][19][20][21][22]. This may be due to relatively small sample sizes and the use of convenience samples of active older adults (n = 69) [20], obese middle-aged men and women (n = 235) [18], college women (n = 294) [19] and young men and women (n = 64) [22].…”
Section: Introductionmentioning
confidence: 99%
“…In our sensitivity analysis we additionally excluded those diagnosed with anxiety or other psychiatric disorders during the first 5 years after inclusion. Nonetheless, it is not possible to eliminate other factors that may lead to reverse causation, such as the influence of individual personality traits to exercise engagement and anxiety disorder vulnerability (11,21,26,69). Therefore, we identify a need for future studies to gain deeper knowledge about the impact of these confounding psychological factors, taking both environmental, genetic, and epigenetic background into account.…”
Section: Discussionmentioning
confidence: 99%
“…Contrariwise, there are also studies indicating that physical activity may not reduce anxiety symptoms (23,24), or at least not as much as psychopharmaceuticals do (23,25). Further, it has been argued that the association between high physical activity and a lower risk of getting diagnosed with anxiety disorders may be driven by reverse causation (26)(27)(28)(29). For instance, anxious symptoms before diagnosis may prevent vulnerable individuals from engaging in physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Walk test performance depends on a variety of factors outside the cardiorespiratory system, namely, age, height, weight, gender, muscle strength, musculoskeletal disorders, nutritional status and cognitive function (Heresi and Dweik, 2011). Even such factors as motivation, agreeableness, anxiety, and the amount of the physical effort expended may influence the walked distance (Hearon and Harrison, 2020). No special encouragement in free-living activities may be the reason why most individuals have not reached the reference walking distance, which is in agreement with the observation in Blagev et al (2019).…”
Section: Concerns Regarding Walk Testingmentioning
confidence: 99%